The Role of Stakeholders in the Development of Tambi Coffee Agroforestry - Miftah Faridl Widhagdha; LV Ratna Devi Sakuntala; Dwiningtyas Padmaningrum (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
The slopes of Mount Tambi turned green again after the efforts to revitalize critical lands carried out by LMDH Argo Mulyo through the development of Tambi coffee agroforestry were successfully initiated from 2010 to 2022. The success of revitalizing critical land in Gunung Tambi certainly did not just happen, because Mount Tambi is a community's living space. has been used for years as a place of livelihood for farming communities who use a seasonal farming system, an agricultural system that is known to be environmentally unfriendly. However, the Tambi coffee agroforestry development model offered by LMDH Argo Mulyo can be a model in utilizing social forestry as a solution to overcome the existing environmental problems. This study reviews the role of stakeholders in efforts to revitalize critical land through the development of Tambi coffee agroforestry using the rapid rural appraisal (RRA) research method. This study conducted an analysis of stakeholder engagement to review the role of stakeholders in the development of tambi coffee agroforestry involving civil society groups, government and the private sector. The success of the development of Tambi coffee agroforestry is evidenced by the increasing social impact in the form of the number of members increasing to 190 people, the economic impact that increases the income of coffee farmers to Rp 35 million per harvest and the environmental impact by increasing the area managed into agroforestry covering an area of 66 hectares.